Asuhan keperawatan keluarga dengan hipertensi di Aceh Besar - Putri, Nadhira Alya; Hidayati, Husna; Arnita, Yuni (Indonesian Journal of Health Science, 2025)
Background: hypertension is one of the health problems in the world which is also referred to as silent killer or silent disease, which is a deadly disease without any signs and symptoms first. Hypertension is also still a top priority in global health. There are several factors that can cause hypertension such as: age, gender, and lifestyle. Objective: this final scientific paper is to provide nursing care to families with hypertension problems. Methods: this study uses a case study with a family nursing care approach which includes assessment, diagnosis determination, intervention, implementation, and evaluation. Results: The family nursing intervention provided was related to five family health tasks, namely identifying problems with hypertension, providing support and motivation to families to care for family members experiencing hypertension problems, simple demonstrations of the DASH (Dietary Approch to Stop Hypertension) diet and hypertension exercises, creating a comfortable living environment, and encouraging families to use nearby health facilities. Conclusion: Family nursing care related to the five family health tasks is very important to improve family knowledge, skills, motivation and improve healthy behaviors in daily life. Suggestion: It is expected that the health center will routinely conduct health checks with the home visit method, especially for family members who have difficulty visiting health facilities. Latar belakangan: hipertensi adalah salah satu masalah Kesehatan di dunia yang juga disebut sebagai silent killer atau silent disease yaitu penyakit yang mematikan tanpa adanya tanda dan gejala terlebih dahulu. Hipertensi juga masih menjadi prioritas utama dalam kesehatan global. terdapat beberapa faktor yang dapat menyebabkan hipertensi seperti: usia, jenis kelamin, dan pola hidup. Tujuan: karya ilmiah akhir ini ialah untuk memberikan asuhan keperawatan pada keluarga dengan masalah hipertensi. Metode: penelitian ini menggunakan studi kasus dengan pendekatan asuhan keperawatan keluarga yang meliputi pengkajian, penetapan diagnose, intervensi, implementasi, dan evaluasi. Hasil: Intervensi keperawatan keluarga yang diberikan terkait dengan lima tugas kesehatan keluarga yaitu mengidentifikasi masalah tentang hipertensi, memberikan dukungan dan motivasi kepada keluarga untuk merawat anggota keluarga yang mengalami masalah hipertensi, demonstrasi sederhana diet DASH (Dietary Approch to Stop Hypertension) dan senam hipertensi, menciptakan lingkungan hidup yang nyaman, serta mendorong keluarga untuk menggunakan fasilitas kesehatan terdekat. Kesimpulan: Asuhan keperawatan keluarga berkaitan dengan lima tugas kesehatan keluarga sangat penting untuk meningkatkan pengetahuan, keterampilan, motivasi keluarga dan meningkatkan perilaku sehat dikehidupan sehari-hari. Saran: Diharapkan kepada puskesmas untuk rutin melakukan pemeriksaan kesehatan dengan metode home visit terutama bagi anggota keluarga yang sulit mengunjungi fasilitas kesehatan.